A Dynamical Reconceptualization of Executive-Function Development - Perone, Sammy; Simmering, Vanessa R.; Buss, Aaron T. (Perspectives on psychological science, 2021)
Executive function plays a foundational role in everyday behaviors across the life span. The theoretical understanding of executive-function development, however, is still a work in progress. Doebel proposed that executive-function development reflects skills using control in the service of behavior—using mental content such as knowledge and beliefs to guide behavior in a context-specific fashion. This liberating view contrasts with modular views of executive function. This new view resembles some older dynamic-systems concepts that long ago proposed that behavior reflects the assembly of multiple pieces in context. We dig into this resemblance and evaluate what else dynamic-systems theory adds to the understanding of executive-function development. We describe core dynamic-systems concepts and apply them to executive function—as conceptualized by Doebel—and through this lens explain the multilevel nature of goal-directed behavior and how a capacity to behave in a goal-directed fashion across contexts emerges over development. We then describe a dynamic systems model of goal-directed behavior during childhood and, finally, address broader theoretical implications of dynamic-systems theory and propose new translational implications for fostering children’s capacity to behave in a goal-directed fashion across everyday contexts.